Well we would need to see some type of graph in order to help you find the slope.
F(x) = 3x + 2x = 3f-1(x) + 2x - 2 = 3f-1(x)(x - 2)/3 = f-1(x)(14 - 2)/3 = f-1(14)12/3 = f-1(14)4 = f-1(14) f(f-1(14)) = f(4)f(4) = 3(4) + 2f(4) = 12 + 2f(4) = 14 A function and its inverse are inverse operations, like addition and subtraction. They undo each other. f(f-1(x) = x
I think that the answer would be D
Three lines is the answer i hope to know the answer
3(6-4y)-2y=1
18-12y-2y=1
18-14y=1
-14y=-17
Y=17/14
Now with a calculator plug in 17/4 multiply it by 4 and subtract the solution from 6 and h get x